2015
DOI: 10.1016/j.amepre.2015.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Poor Mental Health and Reduced Decline in Smoking Prevalence

Abstract: Introduction Although smoking prevalence has been declining for smokers without mental illness, it has been static for those with mental illness. The purpose of this study is to examine differences in smoking rates and trajectories of smoking prevalence in the often-overlooked population of smokers with poor mental health, compared with those with better mental health. Methods Data were obtained from the Behavioral Risk Factor Surveillance System from 2001 to 2010 to examine the relationship between poor men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
40
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 20 publications
3
40
0
Order By: Relevance
“…In the general population, mental health is often measured by indicators of non-specific psychological distress, including symptoms of depression, anxiety, stress, and somatic complaints [9]. Studies in the United States [10][11][12][13] and the United Kingdom [14] have reported psychological distress to be associated with diverging trends in smoking. During the last 10-20 years, smoking rates have declined among those without mental disorders but have remained the same, or declined at a slower pace, among those with mental disorders [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…In the general population, mental health is often measured by indicators of non-specific psychological distress, including symptoms of depression, anxiety, stress, and somatic complaints [9]. Studies in the United States [10][11][12][13] and the United Kingdom [14] have reported psychological distress to be associated with diverging trends in smoking. During the last 10-20 years, smoking rates have declined among those without mental disorders but have remained the same, or declined at a slower pace, among those with mental disorders [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…As smoking prevalence continues to decline in the general population, smoking rates remain intractably high in those with mental health disorders (e.g., Steinberg, Williams, & Li, 2015). For instance, both posttraumatic stress disorder (PTSD) and major depressive disorder (MDD) are characterized by especially high rates of smoking prevalence, heavy smoking, and low quit rates (Feldner, Babson, & Zvolensky, 2007; Lasser et al, 2000; McClave et al, 2009; Weinberger, Mazure, Morlett, & McKee, 2013).…”
mentioning
confidence: 99%
“…The number of smokers remains alarmingly high, and they seem to adapt to indoor smoking bans and continue smoking outdoors. Smoking rates decline less among individuals with mental health problems than in the general population [4][5][6].…”
Section: Introductionmentioning
confidence: 99%